Analisis Variasi Ukuran Partikel Biomassa Cangkang Kelapa Sawit dan Tandan Kosong Kelapa Sawit (TKKS) terhadap Karakteristik Refuse Derived-Fuel (RDF) - Riza Hudayarizka; Wulandari, Agustina; Ariani, Ismi Khairunnissa; Yorika, Rahmi (SPECTA Journal of Technology, 2024)
Energy consumption in Indonesia is still mostly dependent on fossil fuels like coal, leading to their gradual depletion. Therefore, there is a need for environmentally friendly alternative energy sources from biomass waste, such as Refuse Derived-Fuel (RDF). Biomass waste with a high calorific value, like palm kernel shells and empty palm kernel bunches (EFB), is promising as RDF raw material. The size of the particles affects the characteristics of RDF because it impacts the structure and composition of RDF pellets. The tested composition ratios of palm kernel shells, EFB, and adhesives were (90:0:10), (80:10:10), (70:20:10), (60:30:10), and (50:40:10), with particle sizes of 60, 80, and 100 mesh. The RDF characteristics evaluated included moisture content, ash content, volatile matter, fixed carbon, and calorific value. The best RDF composition was found to be 70% palm kernel shells, 20% empty palm kernel bunches, and 10% adhesive at a particle size of 60 mesh, resulting in a moisture content of 5.2%, ash content of 4.64%, volatile matter of 78.89%, fixed carbon of 9.64%, and a calorific value of 4404.32 cal/g. XRD analysis indicates that RDF contains amorphous carbon, silica, and, with the addition of EFB, contributes to the potassium content. SEM analysis shows that larger particle sizes of the raw material form larger pores in RDF compared to smaller particle sizes.